Victim identification application with face recognition based on android. Issue 1 (March 2021) - Triyono, L; Handoko, S; Puspawaty, K Y
Abstract: The increase in the population causes the problems faced are also increasing. Problems that arise include that, the number of accident victims who have recently often occurred on the highway, where the victims of the accident suffered minor injuries to severe and some even have to take lives due to accidents on the highway. And the second is crime, like a murder case that can take someone's life. Often victims do not carry identities, making it difficult for the police or related parties to identify victims of accidents and killings. This system is made in the hope that it can help the police or related parties to be able to recognize the face of the victim without an identity just by using the android application. So that it can save more time in identifying the identity of the victim. Victim face recognition algorithm using Facial Landmark Detector and for its implementation using the Dlib library. To do facial recognition, it is done by taking Figures of victims using an application on android which is then sent to the server for the recognition process. After the image is sent to the server, the recognition process will be carried out, the results of the introduction process are sent back to android to display the results. The level of accuracy of the victim's face recognition with a wound if using a tolerance of 0.35 is 100%, but if using tolerance 0.2 the level of accuracy is only 25%.